Bioassay methods in natural product research and drug development. Lars Bohlin and Jan G. Bruhn Ed. Kluwer Academic Publishers, The Netherlands, 1999,201 p. - Lock de Ugaz, Olga (2000)
El artículo no presenta resumen.